Streamlining Digital Identity Ecosystem in Nepal: A Private Blockchain Approach - Acharya, Praches; Sapkota, Binod; Thokar, Bibat; Dawadi, Babu Ram (International Journal on Engineering Technology and Infrastructure Development, 2025)
As digitization continues to expand into various aspects of human life, the need for ro- bust user authentication becomes crucial to ensure secure online and digital services. However, the process of verifying one’s identity has become increasingly complex and burdensome, contradicting the initial intentions of simplifying procedures through digitization. This research paper addresses the challenges associated with digital identity verification and proposes an innovative solution. This solution introduces a digital identity ecosystem powered by a private blockchain network, aiming to revolutionize identity management and authentication processes. By leveraging the decentralized and immutable nature of blockchain technology, this approach simplifies and secures the establishment and verification of digital identities, replacing reliance on physical identification methods. Through an extensive literature review and analysis of existing identity management systems, this research empha- sizes the advantages of utilizing a private blockchain network for identity authentication. It explores the benefits of decentralization, data immutability, and enhanced security provided by blockchain tech- nology, which can alleviate the complexity associated with current authentication methods. The pro- posed solution holds the potential to streamline authentication procedures, unlocking the true potential of digitization by making identity management more efficient, convenient, and secure for both individuals and service providers.